Judicial practice as form of providing of law and order in the field of competition - Корчак, Н. М. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In the article the forms of judicial practice are analysed as a source of the legal adjusting of relations inthe field of competition and specified on the necessity of differentiating of concepts «Legal precedent»,«analogic decision» and «court decision».